The Incredible Dash - Shealy, Dennis R., 1969-; Disney Global Artists (New York : Random House, 2004)
The Incredibles, a family which appears normal but whose members have super powers, confront the evil Syndrome.
Accelerated Reader AR
Keywords: Heroes -- Fiction; Identity -- Fiction